Men Don’t Cry, Women Do? A Myth Exploration of the Archetypes of Contemporary American Novel Grieving Characters - Anam, Zuhrul; Darmawan, Ruly Indra (Universitas Teknokrat Indonesia, 2024)
The examination of grieving archetypes in contemporary American novels is crucial for understanding the cultural myths surrounding emotional expression, particularly the stereotype that